Trucks Are Valuable Auxiliary Haulage Units in Rail Pits For: - G. J. Ballmer (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1951)
Trucks Are Valuable Auxiliary Haulage Units in Rail Pits For: ( I ) Making railroad grades (2) Establishing benches (3) Making new dropcuts